Development of a Novel Model of Soil Legacy P Assessment for Calcareous and Acidic Soils - Yu, Wenjia; Li, Guohua; Hartmann, Tobias Edward; Xu, Minggang; Yang, Xueyun; Li, Haigang; Zhang, Junling; Shen, Jianbo (Frontiers in Environmental Science, 2021)
Phosphate (P) rock is a finite natural resource, and its use for P fertilizer production has resulted in its rapid depletion worldwide. In order to reduce the use of natural P resources, reducing the input of P into agricultural systems is necessary. The assessment of legacy P in soil is an option to maintain crop yield with low P fertilizer input. Many models have been tested to assess the contribution of legacy soil P to crop uptake. However, these models face a common challenge as conceptual soil P pools in models cannot be accurately initiated and evaluated using measured soil P indexes. In this study, a novel legacy P assessment (LePA) model was developed according to empirical equations about crop P uptake, soil Olsen-P, and total P from two long-term fertilizer experiments in typical calcareous and acidic soils in China. We used the DPPS (dynamic phosphorus pool simulator) model as a contrast model to estimate the simulation accuracy of the new LePA model. The calibration and validation datasets for both models were set-up by collecting data from two long-term fertilizer experiments in typical calcareous and acidic soils in China. The results showed that the LePA model simulated crop P uptake similar to the DPPS model in calcareous soil. While the DPPS model failed to depict crop P uptake under low pH conditions, the LePA model worked well after modification when limited crop growth caused by acidic conditions was considered. Moreover, the LePA model can also predict changes in soil TP and Olsen-P with P fertilizer application, which are new functions compared with the DPPS model. Based on a scenario analysis generated by the LePA model, P fertilizer application could be reduced by 52% in Yangling and 46% in Qiyang compared with the conventional application rate during this period to maintain the current yields if soil legacy P can be utilized efficiently. The LePA model is a useful tool for guiding soil P management from the field to country scales.